Experimental Study on Structural Behaviour of Glulam Beams Pre-stressed by Compressed Wood - Buan Anshari; Akihisa Kitamori; Kiho Jung; Kohei Komatsu (Masyarakat Peneliti Kayu Indonesia, 2011)
This paper presents the study on structural behaviour of glulam beams pre-stressed by compressed wood (CW) in terms of load carrying capacity, strength and stiffness. Glulam beams were strengthened by inserting CW blocks into the pre-cut rectangular holes on the top of the beams. This practice was to make use of moisture-dependent swelling nature of the compressed wood. The CW block was placed in a way in which its radial direction was coincident with the longitudinal direction of the beam to be strengthened. After pre-stressing process, all beams were placed in a chamber with Relative Humidity (RH) fluctuated between 40% until 80% and a constant temperature of 20⁰C until the maximum swelling of the CW block was reached. The glulam beams with the size of 3800 mm long, 200 mm deep and 120 mm wide were reinforced by 3, 5, 7 CW blocks respectively, all with the same thickness of 45 mm. In addition, there were two beams which were reinforced at the bottom extreme fibre with one lamella made of compressed wood. There were also three beams without any reinforcement for control purpose. The test results showed that a pre-camber was produced in the mid-span of the beam reinforced. At both the top and the bottom extreme fibres of the beam significant initial tensile and compressive stresses were generated respectively. Bending tests indicated that the load carrying capacity of the reinforced beams increased significantly in comparison to the beam without reinforcement.